Passion, grit, and mindset in undergraduate sport sciences students. (August 2021) - Frontini, Roberta; Sigmundsson, Hermundur; Antunes, Raul; Silva, Ana Filipa; Lima, Ricardo; Clemente, Filipe Manuel
Abstract: The aim of this study was two-fold: (i) to compare passion, grit and mindset between sexes; and (ii) to analyze the relationships between passion, grit and mindset. Fifty-eight men (age: 20.10 ± 2.70 years old) and forty-eight women (age: 19.27 ± 4.10 years old) sports sciences undergraduate students voluntarily participated in this study. A cross-sectional survey design was followed. The passion scale, grit scale and mindset scale were provided to participants. Comparisons in the passion, grit and mindset items revealed no significant differences between sexes (p > 0.05). Relationships between passion, grit and mindset were tested. Overall (both sexes considered), correlations presented small magnitudes in the pair's passion*grit (r = 0.28; 95%CI [-0.07; 0.31]; p = 0.004), passion*mindset (r = 0.203; 95%CI [0.01; 0.38]; p = 0.043) and grit*mindset (r = 0.06; 95%CI [-0.14; 0.25]; p = 0.574). As conclusions, the present study did not find significant differences in passion, grit and mindset between sexes in undergraduate sports sciences students. Additionally, it was verified that relationships between passion, grit and mindset are small in this population.